Diabetes Distress in Young Adults with Type 2 Diabetes: A Cross-Sectional Survey in China - Yanfen Hu; Lingxia Li; Jun Zhang (Journal of Diabetes Research)
Background. Diabetes distress is a negative emotion related to diabetes management, which can compromise self-care and management of diabetes. However, few studies on diabetes distress have focused on young adults with type 2 diabetes in China. Methods. A cross-sectional survey was conducted. Using a convenient sampling method, 98 young adults with type 2 diabetes who were admitted to our hospital from June 2017 to July 2018 were selected as research subjects. They were investigated using a basic demographic questionnaire, Diabetes Distress Scale, Summary of Diabetes Self-Care Activities Measure, and Audit of Disease Knowledge. Pearson’s correlation analysis and regression analysis were used to analyze the influencing factors of diabetic distress. Results. Among participants, 90.82% suffered from diabetes distress with an average score of 3.01±0.58. Regimen-related, emotional burden-related, and interpersonal-related distress were the most frequently reported as severe. The results of the single-factor analysis showed that gender (P=0.019), age (P=0.003), occupation (P=0.022), smoking (P<0.001), and diabetes complications (P=0.001) were the main factors affecting diabetes distress. The correlation analysis showed that diabetes distress was negatively correlated with the level of diabetic self-management (P<0.001, r=−0.377) but not with the level of diabetes knowledge (P=0.052, r=−0.197). The results of a multiple regression analysis showed that self-management level (P=0.001, 95% CI: -0.039-0.011), age (P=0.002, 95% CI: -0.463-0.104), smoking (P=0.018, 95% CI: -0.504-0.048), and complications (P=0.009, 95% CI: -0.517-0.076) accounted for 35.42% of the total variation in diabetes distress. Conclusion. Young adults with type 2 diabetes reported severe diabetes distress. Age, smoking, and diabetes complications were the main factors influencing diabetes distress in young adults with type 2 diabetes. Results of the present study are fundamental in selecting targeted measures for alleviating diabetes distress and thus improving the quality of life in these patients.